Integration Of Digital Campaigns, Experiential Events, And Brand Support In Raising Awareness Of Early Detection Of Breast Cancer - Aji, Imanuel Deny Krisna; Nathania, Jovita (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the influence of digital campaigns, events, and brand support on awareness of early detection of breast cancer in the social movement